Prevention of HIV-1 Infection with Early Antiretroviral Therapy - Cohen, Myron S; Chen, Ying Q; McCauley, Marybeth; Gamble, Theresa; Hosseinipour, Mina C; Kumarasamy, Nagalingeswaran; Hakim, James G; Kumwenda, Johnstone; Grinsztejn, Beatriz; Pilotto, Jose H.S; Godbole, Sheela V; Mehendale, Sanjay; et al. (The New England journal of medicine, 2011)
In this large, international study of HIV-1–serodiscordant couples, the receipt of antiretroviral therapy by the infected partner decreased transmission to the uninfected partner as well as rates of clinical events in the HIV-1–infected partner. Combination antiretroviral therapy decreases the replication of human immunodeficiency virus type 1 (HIV-1) and improves the survival of infected persons. 1 , 2 Such therapy has been shown to reduce the amount of HIV-1 in genital secretions. 3 – 5 Because the sexual transmission of HIV-1 from infected persons to their partners is strongly correlated with concentrations of HIV-1 in blood 6 and in the genital tract, 7 it has been hypothesized that antiretroviral therapy could reduce sexual transmission of the virus. Several observational studies have reported decreased acquisition of HIV-1 by sexual partners of patients receiving antiretroviral therapy. 8 – 11 These results have been extrapolated to . . .